Chromogranin A provides additional prognostic information in children with severe hand, foot, and mouth disease: A prospective observational study. (April 2020) - Dang, Hongxing; Li, Jing; Liu, Chengjun; Xu, Feng
Highlights: The chromogranin A (CHGA) level in severe hand, foot, and mouth disease (HFMD) was found to be associated with neurogenic pulmonary edema and cardiopulmonary failure. CHGA levels correlated with disease severity and a poor prognosis of the disease. CHGA might have a certain early predictive value with high specificity and sensitivity for mortality in cases with severe HFMD. Abstract: Objective: Severe hand, foot, and mouth disease (HFMD) is associated with high mortality in children, and persistent sympathetic activation is a common presentation. The aim of this study was to prospectively investigate serum chromogranin A (CHGA) levels and their prognostic role in this condition. Methods: Serum CHGA, creatine kinase myocardial band (CK-MB), serum D-dimer, norepinephrine, blood glucose, lactate, and C-reactive protein levels, white blood cell (WBC) counts, usage of vasopressors, pediatric risk of mortality Ⅲ (PRISM-Ⅲ) scores, and viral etiology were measured upon pediatric intensive care unit (PICU) admission. The correlation between clinical outcomes and the indicators listed above were analyzed, and the ability of CHGA as a biomarker to predict mortality was evaluated. Results: Serum CHGA levels were higher in the non-survivors group than in the survivors group (median (interquartile range): 434.8 (374.3–502.4) vs 183.3 (131.9–246.9) μg/l; p  < 0.001) and were correlated with norepinephrine ( r  = 0.37. p  < 0.001), blood glucose ( r  = 0.32, p  = 0.001), lactate ( r  = 0.25, p  = 0.009), WBC ( r  = 0.20, p  = 0.039), and PRISM-Ⅲ scores ( r  = 0.748, p  < 0.0001). Patients suffering neurogenic pulmonary edema, those infected with enterovirus A71, and those requiring more vasopressors had higher serum CHGA levels (median (interquartile range): 385 (239.9–488.8) vs 161 (115.6–222.9), 340.6 (190.6–436.0) vs 150.5 (112.1–210.0), 395.6 (209.1–487.0) vs 167.7 (110.5–240.5) μg/l, respectively; p  < 0.0001). The CHGA level upon PICU admission in severe HFMD could be an independent risk factor for mortality (adjusted odds ratio 2.459, 95% confidence interval 1.054–5.906, p  = 0.038) with high specificity (87.5%) and sensitivity (82.6%) (cut-off value at 339.6 μg/l). Conclusions: The CHGA level in severe HFMD was found to be associated with cardiopulmonary failure. If measured upon PICU admission, CHGA may provide additional prognostic information in this disease.